ผลของการให้ข้อมูลร่วมกับการประคบด้วยความเย็นต่อความเจ็บปวดในผู้ป่วยกระดูกไหปลาร้าหัก - อัญชลี ศรีเทพ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The purpose of this quasi-experimental research was to examine the effect of giving information combined with cryotherapy on patients with fracture clavicle. The study samples were 40 fracture clavicle patients surgical wards, Trang Hospital. A matched-pair technique was used to assign patients to experimental and control groups. Each group consisted of 20 patients. The two groups were matched in age, weight, and frequency of medicine for pain control. The control group received usuall nursing care while the experimental group received the giving information combined with cryotherapy and usual Numeric Rating Scale (NRS) was used to measure pain level after cold compress at the 4th and the 8th hour. Data were analyzed using descriptive statistics, Repeated measures analysis of variance and Independent t-test. Major findings were as follow: 1. The posttest mean score of pain at the 4th and the 8th hour after receiving the providing information combined with cryotherapy were significantly lower than those of the pretest phase (p<.05) 2. The decreasing pain score at the 4th and the 8th hour were significantly greater than those of the control group (p<.05)